Criminal Liability Resulting In Serious Injury To The Child As The Victim (Case Study Of District Court Decision No. 000 / Pid.Sus/2022/PN.Mdn) - Fitriana, Fitriana (Legalpreneur Journal, 2022)
Crimes against “persons " in the Criminal Code include the following; honor (humiliation), revealing secrets, personal freedom or Independence, life, body or body, property or wealth but in relation to children there are special rules about crimes that affect children. This thesis is entitled “accountability of violent abuse resulting in serious injury to the child as a victim (Case Study Medan District Court Decision No. 000 / Pid.Sus / 2022 / Fr.Mdn). The problems in this thesis is the regulation of criminal acts of abuse / violence that resulted in serious injury, criminal liability terahap paenganiahan criminal violence against children as koraban terahap and the application of the law on perpetrators of crime. The purpose of this study was to determine the legal arrangements against the crime of abuse resulting in serious injury, to determine criminal liability against perpetrators of crimes of abuse resulting in serious injury, to determine the application of the law against perpetrators of violent abuse resulting in serious injury to children as victims according to Medan District Court Decision No. 000 / Pid.Sus/2022/Fr.Mdn. The research method used in the writing of this thesis is normative legal research conducted by means of library research. The results of this study indicate that the crime of abuse resulting in serious injury is regulated in Article 80 paragraph (2) Jo. Article 76C of Law No. 35 of 2014 on amendments to Law No. 23 of 2002 on Child Protection on violence resulting in serious injury that based on the facts revealed at the hearing, and with the conviction of the judge, the verdict handed down in this case is imprisonment for 1 (one ) year 6 (six) months, a fine of Rp. 50.000.000,00. (fifty million rupiah) with the provision that if the fine is not paid, replaced imprisonment for 3 (three) months each.